2009
DOI: 10.1016/j.brainres.2009.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Chronic electrical stimulation of the contralesional lateral cerebellar nucleus enhances recovery of motor function after cerebral ischemia in rats

Abstract: Novel neurorehabilitative strategies are needed to improve motor outcomes following stroke. Based on the disynaptic excitatory projections of the dentatothalamocortical pathway to the motor cortex as well as anterior and posterior cortical areas, we hypothesize that chronic electrical stimulation of the contralesional dentate (lateral cerebellar) nucleus output can enhance motor recovery after ischemia via augmentation of perilesional cortical excitability. Seventy five Wistar rats were pre-trained in the Mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
64
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(71 citation statements)
references
References 43 publications
(48 reference statements)
4
64
0
Order By: Relevance
“…Brain tissue was freeze-sectioned in the transverse plane of electrode penetrations. Every fourth section, each 40 m in thickness, was stained with thionine to reveal cell bodies, whereas its adjacent section was stained with Perls' solution, enhanced by 3,3=-diaminobenzidine (Perls/ DAB), to reveal the ferric iron caused by rupture of small blood vessels or by the electrolytic lesion-associated electrocoagulation (Machado et al 2009;Russo and Bruce 2000). Histology was performed by NeuroScience Associates (Knoxville, TN).…”
Section: Surgeries and Experimental Setupmentioning
confidence: 99%
“…Brain tissue was freeze-sectioned in the transverse plane of electrode penetrations. Every fourth section, each 40 m in thickness, was stained with thionine to reveal cell bodies, whereas its adjacent section was stained with Perls' solution, enhanced by 3,3=-diaminobenzidine (Perls/ DAB), to reveal the ferric iron caused by rupture of small blood vessels or by the electrolytic lesion-associated electrocoagulation (Machado et al 2009;Russo and Bruce 2000). Histology was performed by NeuroScience Associates (Knoxville, TN).…”
Section: Surgeries and Experimental Setupmentioning
confidence: 99%
“…By targeting it at its node of origin in the dentate nucleus or the ascending pathway, the majority of the tract can be activated with a single implanted multipolar electrode [69]. Invasive, subthreshold stimulation, delivered chronically at lower frequencies (in the beta range) can generate sustained facilitatory effects upon excitability of M1 [70] and promote recovery of the impaired forelimb to a significantly greater degree than in a control [71,72].…”
Section: Methodological: Targeting Peri-lesional Substrates Even Whilmentioning
confidence: 99%
“…Deep brain stimulations targeting the thalamus (Th) and periaqueductal gray matter for post-stroke movements and neuropathic pain have demonstrated efficacy in human studies [59][60][61]. Deep brain stimulations in the cerebellar dentate nucleus in rats have also been shown to promote post-stroke recovery and enhance synaptic plasticity and reorganization in the perilesional cortex [62][63][64][65].…”
Section: Current Brain Stimulation Techniques Used To Study Stroke Rementioning
confidence: 99%
“…2). Electrical stimulation of the dentate nucleus in rats has been shown to promote recovery and enhance plasticity [62][63][64][65]. Tracing studies using the rabies virus have indicated that different divisions of the dentate nucleus mediate different functions.…”
Section: Benefits Of Optogeneticsmentioning
confidence: 99%